2019
DOI: 10.1021/acsaem.9b01064
|View full text |Cite
|
Sign up to set email alerts
|

NiFe Layered Double Hydroxide on Nitrogen Doped TiO2 Nanotube Arrays toward Efficient Oxygen Evolution

Abstract: Enormous efforts have been devoted to the development of new catalysts or unique nanostructures with high activity and stability at low cost for oxygen evolution reaction (OER). Herein, we designed the fabrication of NiFe layered double hydroxide (LDH) nanoplates supported on nitrogen doped TiO 2 nanotube arrays as a superior OER electrocatalyst and investigated the impacts of NiFe-LDH loading and nitrogen doping concentration on electrocatalytic performance. When the load and nitrogen content are 0.6 mg cm −2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…One strategy to improve intrinsic catalytic activities of transition metal-based OER catalysts is the synthesis of mixed transition metal-based materials, which could outperform their single-component counterparts. The NiFe-based catalysts are particularly promising since both Ni and Fe are earth-abundant transition metals, and addition of an appropriate amount of Fe into Ni-based catalysts could greatly increase their OER activities. Recent studies have shown that various NiFe-based compounds, including their oxides and oxyhydroxides, and their hybrids formed by adding other components, can show high OER catalytic activities. However, their performance still needs significant improvement due to their low conductivity and small catalytically active surface area. The NiFe alloys could be an attractive option to address these challenges in terms of tunable content of Fe and excellent conductivity; in particular, the catalytically active sites of NiFe oxides/(oxy)­hydroxides could be derived from their surfaces spontaneously both in the ambient environment and during the anodic oxidation. ,, Until now, there have been only a few studies using NiFe alloys as OER catalysts, and the reported ones still have relatively low activities. ,, Several great challenges exist for significantly improving their OER activities: (1) NiFe alloy NPs with greatly reduced size have significantly increased surface area (researchers are even reducing the size of OER catalysts to the single-atom level to increase the number of exposed active sites), but they easily aggregate to reduce the accessible active sites on them and inhibit the mass diffusion; , (2) the electron transfer/transport between these alloys and the electrode is slow and needs to be greatly accelerated; , (3) both strong reducing agents and large surfactants are required to create the non-noble NiFe alloy NPs, making the synthesis process nonenvironmentally friendly and complicated; , (4) approaches to controllably synthesize NiFe alloy NPs for optimizing their OER activities are still lacking. , …”
Section: Introductionmentioning
confidence: 99%
“…One strategy to improve intrinsic catalytic activities of transition metal-based OER catalysts is the synthesis of mixed transition metal-based materials, which could outperform their single-component counterparts. The NiFe-based catalysts are particularly promising since both Ni and Fe are earth-abundant transition metals, and addition of an appropriate amount of Fe into Ni-based catalysts could greatly increase their OER activities. Recent studies have shown that various NiFe-based compounds, including their oxides and oxyhydroxides, and their hybrids formed by adding other components, can show high OER catalytic activities. However, their performance still needs significant improvement due to their low conductivity and small catalytically active surface area. The NiFe alloys could be an attractive option to address these challenges in terms of tunable content of Fe and excellent conductivity; in particular, the catalytically active sites of NiFe oxides/(oxy)­hydroxides could be derived from their surfaces spontaneously both in the ambient environment and during the anodic oxidation. ,, Until now, there have been only a few studies using NiFe alloys as OER catalysts, and the reported ones still have relatively low activities. ,, Several great challenges exist for significantly improving their OER activities: (1) NiFe alloy NPs with greatly reduced size have significantly increased surface area (researchers are even reducing the size of OER catalysts to the single-atom level to increase the number of exposed active sites), but they easily aggregate to reduce the accessible active sites on them and inhibit the mass diffusion; , (2) the electron transfer/transport between these alloys and the electrode is slow and needs to be greatly accelerated; , (3) both strong reducing agents and large surfactants are required to create the non-noble NiFe alloy NPs, making the synthesis process nonenvironmentally friendly and complicated; , (4) approaches to controllably synthesize NiFe alloy NPs for optimizing their OER activities are still lacking. , …”
Section: Introductionmentioning
confidence: 99%
“…) is mainly ascribed to its ultrathin sheet morphology, so it can better adhere to the surface of glassy carbon electrode and reduce shedding during the OER test. 44 All these pertinent electrocatalytic parameters exhibited by U-LDH(SO 4 2À ) are better than those drived from the conventional NiFe-LDHs and the Fe/Ni-based catalysts ( ) unveiled only minor changes aer 1000 cyclic voltammetry (CV) cycles (Fig. 4a), further implying its good electrochemical stability for OER.…”
Section: àmentioning
confidence: 95%
“…Among them, LDHs (hydroxides) are known as a type of the most excellent alkaline OER catalysts. 14,15 Unfortunately, HER performance of NiFe LDH always cannot live up to the expectation, for the lack of active sites and poor conductivity. 16,17 But in practice, using the same catalyst for anodic and cathodic electrodes can promote fabrication efficiency and reduce manufacturing costs.…”
Section: Introductionmentioning
confidence: 99%